Examining the Quality Performance of Indigenous and Expatriate Contractors in Nigeria: Clients’ Perspective: Array - Ajayi, Akeem Adunfe; Babalola, Olubola; Oyeyipo, Opeyemi; Anjorin-Ohu, Adeyemi (The Journal of Accounting and Management, 2021)
The Nigerian construction industry is faced with considerable amounts of pressure to improving quality performance. While there exist considerable number of studies that have examined factors influencing quality performance practices in various domains, these are not necessarily applicable to the construction companies in Nigeria. Hence, this empirical research assessed factors affecting the quality performance of indigenous and expatriate construction companies from the perception of clients. A cross-sectional research design was adopted. Following a systematic literature review in identifying the extant factors affecting quality performance, questionnaire survey was carried out to assess the level of agreement of the respondents. Purposive sampling techniques was used to obtain data from the target respondents. One hundred and nineteen copies of complete questionnaire were gotten and used for this study using descriptive and inferential analytical tools. The findings revealed sixty-four factors affecting quality performance in which analysis led to the conclusion that consistent payment of works done as at when due as well as the experience of the contractors at the works are necessary conditions that ensure good quality performance.